EFFORTS TO OPTIMIZE THE OPERATION OF THE DADAHUP LOWLAND IRRIGATION AREA IN CENTRAL KALIMANTAN - Asril Zevri; Adam Pamudji Rahardjo; Djoko Legono (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
ABSTRACT Dadahup lowland irrigation area is one of the areas developed as a food estate. Land cover change to shrubs is caused by channels with buildings that are not functioning optimally, so it is often hit by floods and droughts. One of the efforts to improve the function of channels and buildings is to control the minimum water level of 60 cm in the dry season and the maximum water level of 10 cm in the rainy season. This study aims to determine the optimal operations and maintenance through adjusting the elevation of the gate opening to achieve the quantity and quality for the development of water management systems in lowland irrigation. The research method was carried out with hydraulic simulation based on the tides of the Barito River Mouth, discharge, rainfall, and pH obtained from telemetry monitoring system with openings of all sluice gates in primary channels and secondary channels. The results showed that operation and maintenance optimization can be done by setting primary and secondary sluice gates that are opened at a water level elevation above + 0.5 m in the dry season as supply and water level elevation + 1.1 m in the rainy season as drainage. Primary and secondary sluice gates are closed at water levels below + 0.5 m to maintain water levels and water quality.Keywords optimization, lowland, Dadahup Lowland Irrigation Area , HEC-RAS, hydraulic ABSTRAKDaerah irigasi rawa Dadahup merupakan salah satu daerah yang dikembangkan sebagai lumbung pangan. Perubahan tutupan lahan menjadi semak belukar disebabkan oleh saluran dengan bangunan yang tidak berfungsi secara optimal sehingga sering dilanda banjir dan kekeringan. Salah satu upaya untuk meningkatkan fungsi saluran dan bangunan adalah dengan mengendalikan tinggi muka air minimum 60 cm pada musim kemarau dan tinggi muka air maksimum 10 cm pada musim hujan. Penelitian ini bertujuan untuk mengetahui pola operasi dan pemeliharaan yang optimum melalui pengaturan pintu dalam mencapai kuantitas dan kualitas air yang sesuai untuk pengembangan sistem tata air di lahan irigasi rawa. Metode penelitian dilakukan dengan simulasi hidraulika berdasarkan pasang surut muara Sungai Barito, debit, curah hujan, dan pH yang diperoleh dari sistem monitoring telemetri dengan bukaan setiap pintu air pada saluran primer serta saluran sekunder. Hasil penelitian menunjukkan bahwa optimasi operasi dan pemeliharaan dapat dilakukan dengan pengaturan pintu air primer dan sekunder yang dibuka pada elevasi muka air di atas + 0,5 m pada musim kemarau sebagai supply dan elevasi muka air + 1,1 m pada musim penghujan sebagai drainase. Pintu air primer dan sekunder ditutup pada elevasi muka air di bawah + 0,5 m untuk menjaga tinggi muka air dan kualitas air.Kata Kunci: optimasi, rawa, Daerah Irigasi Rawa Dadahup, HEC-RAS, hidrolika